Identification of fruit forms using CAPS marker among the oil palm indigenous germplasm: Identification of fruit forms using CAPS marker among the oil palm indigenous germplasm - M V B VENU,; B KALYANA BABU, (Journal of Oilseeds Research, 2020)
In the present study we aimed at molecular identification of three fruit forms among indigenous oil palm germplasm. We have developed CAPS marker that could be used for distinguishing all the three fruit forms of oil palm at seedling stage which saves a lot of time and space. The developed marker system was tried with 50 indigenous oil palm germplasm and the developed CAPS marker identified 20 genotypes as dura, 22 as tenera, 8 as pisifera lines. The results showed that the markers identified are able to clearly characterize the dura and pisifera genotypes.